Labor Conditions in Meat Packing and the Recent Strike - Commons, John R. (Quarterly Journal of Economics, 1904)
Journal Article Labor Conditions in Meat Packing and The Recent Strike Get access John R. Commons John R. Commons University of Wisconsin Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 19, Issue 1, November 1904, Pages 1–32, https://doi.org/10.2307/1884862 Published: 01 November 1904